Islamisasi Prinsip Counter Accounting - Dayno Utama (Islamica: Jurnal Studi Keislaman, 2017)
The purpose of this study is to explore the idea of Islamization of counter accounting principles. Such an Islamization is necessary because counter accounting princip-les are formulated by using the philosophy of punk from the western society which has different beliefs. In addition, the idea of Islamization in this study shows that Islamic knowledge can indeed be developed continuously. Therefore, the claim that there is no development inside this knowledge, and that it cannot be categorized as science, willl no longer exist. This study reveals the findings that the wisdom from argumentation which constructs the principles of counter accounting is parallel with the wisdom from Islamic values as interpreted by experts of Islamic accounting. The Islamiza-tion of counter accounting principles confirms the truth of belief in the existence of Allah and His revelation.